The role of mucin cell-free DNA detection as a new marker for the study of acellular pseudomyxoma peritonei of appendicular origin by liquid biopsy. (June 2020) - García-Olmo, Damián; Olmedillas-López, Susana; Cortés-Guiral, Delia; Villarejo, Pedro; López Rojo, Irene; Guadalajara, Héctor; García Gómez-Heras, Soledad; García-Arranz, Mariano
Background: Acellular pseudomyxoma peritonei ( a PMP) is a rare peritoneal malignancy characterized by the accumulation of large amounts of mucin (lacking tumor cells) in the peritoneum. Many cases account for several kilograms of mucin to be screened by the pathologist. This is a comprehensive study of three patients with a PMP, whose tumors showed KRAS mutation, allowing for the tracking of this marker by liquid biopsy. Methods: Pre and post-surgery plasma, and mucin removed during cytoreductive surgery were collected from the patients. KRAS mutations were analyzed using droplet digital polymerase chain reaction (ddPCR). Mucin was injected in mice. KRAS and cytokine levels were measured in plasma of the mice using ddPCR and a magnetic bead-based assay. Mucin microbiome was analyzed by 16S rRNA sequencing. Results: KRAS mutations were detected in mucin cell-free DNA (cfDNA) from the three patients but not in the pre or post-surgery plasma. Electron microscopy detected microparticles (diameter <0.4 µm) in mucin. Mucin from one patient grew up inside the peritoneal cavity of mice and human KRAS was identified in mucin cfDNA, but not in plasma. All mucins showed the same bacterial profile. Cytokine levels were slightly altered in mice. Conclusions: The three a PMP patients included in this study shared some common aspects: the absence of tumor cells in mucin, the presence of KRAS mutated cfDNA in mucin, and the absence of this tumor-derived mutation in the bloodstream, providing additional information to the routine pathological examinations and suggesting that mucin cfDNA could potentially play a role in a PMP recurrence and prognosis.